PENGEMBANGAN MEDIA INTERAKTIF BERBASIS GAME EDUKASI BAAMBOOZLE PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS VI MI TARBIIYAH ISLAMIYAH PALEMBANG (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is a Research and Development (R&D) development study. This study aims to determine the process, level of validity, and level of effectiveness of interactive media based on educational games Baamboozle in Indonesian language subjects in grade VI MI Tarbiyah Islamiyah Palembang. This type of research uses the ADDIE development model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques used are questionnaires, tests, and documentation. The results of the study showed that the use of interactive media based on educational games baamboozle was considered very valid with the assessment of media experts obtaining an average score of 86.66%, material experts obtained an average score of 98%, language experts obtained an average score of 82% so that all three met the criteria of